Comparison of the Chloroplast Genome Sequences of 13 Oil-Tea Camellia Samples and Identification of an Undetermined Oil-Tea Camellia Species From Hainan Province - Chen, Jing; Guo, Yujian; Hu, Xinwen; Zhou, Kaibing (Frontiers in Plant Science, 2022)
The cpDNA of 13 samples of oil-tea camellia from South China was sequenced and resequenced, and divergence hotspots and simple sequence repeat (SSR) variation characteristics were analyzed. The cpDNA was 156512~157089 bp in length and had a circular tetrad structure typical of angiosperms.The cpDNA sequences of undetermined species of oil-tea camellia from Hainan Province and the population of Camellia gauchowensis from Xuwen County were identical. In total, 136 genes were annotated. The small single-copy (SSC)/IR boundary was rich in variation. Divergence hotspots were mainly located in the intergenic space and CDSs, and there were obvious differences in the divergence hotspots among species. The same divergence hotspots were found in Camellia vietnamensis, Camellia gauchowensis and the undetermined species of oil-tea camellia from Hainan Province. A total of 191~198 SSR loci were detected. Different species had common SSRs and unique SSRs. Based on cpDNA, CDSs and non-CDSs, the evolutionary relationships of different species of Camellia could be well identified.Camellia vietnamensis was more closely related to the undetermined species of oil-tea camellia from Hainan Province and the population of Camellia gauchowensis from Xuwen County than to the population of Camellia gauchowensis from Luchuan County. Camellia osmantha was closely related to Camellia gauchowensis and Camellia vietnamensis. In conclusion, cpDNA of different oil-tea camellia species has a conserved tetrad structure, with certain length polymorphisms. SSRs are expected to be developed as "barcodes" or "identity cards" for species identification. SSR variation and other factors result in abundant divergence hotspots in the CDSs and intergenic space (one non-CDS region), which indicates that cpDNA, CDSs and non-CDSs can be used for species identification and phylogenetic analysis of Camellia. Accordingly, the undetermined species of oil-tea camellia from Hainan Province is likely Camellia vietnamensis. Camellia vietnamensis and Camellia gauchowensis may be the same species. Other genetic evidence is needed to determine whether Camellia osmantha is a new independent species. The previous division of related sections of Camellia may need to be readjusted based on cpDNA sequences.